A morphological analysis of Lun Bawang / Shalini Mugundan - Shalini , Mugundan (2020)
Linguists generally acknowledge that there exists an inevitable inter-relationship between different levels of linguistic analysis; phonetics, phonology, morphology, syntax, and semantics. Various linguistic labels are used to describe such a link. In particular, there exists a bridge between the phonology and morphology of particular languages. The term morphophonemic is generally used to describe linguistic statements that can be made of the phonemic structure of morphemes and their effect on the grammatical content of languages. This research attempts a morphophonemic analysis in one Austronesian language which is known as Lun Bawang, a language own by Lun Bawang or Murut community in the Sarawak region. This language also falls under one of the endangered languages in the Brunei region. The research has been conducted by analyzing the morphological processes involved in this language. The lexical categories or word classes have been identified and used as the medium of analysis. Besides, this research has also been a bridge to see the morphological patterns of Lun Bawang with the reference of bahasa Melayu as bahasa Melayu is the main language under the Austronesian family. The data have been analyzed by doing broad transcription. The result indicates that Lun Bawang has quiet similar morphological patterns as bahasa Melayu as most of the words are seen to be used in both languages. On the other hand, Lun Bawang has been identified to have a few morphological processes such as affixation and reduplication and phonemically has some similarities whereby bahasa Melayu has undergone complete transfer, partial transfer, transfer with sound changes, and few more components to fit Lun Bawang sound system. Overall, Lun Bawang is a language that also falls under the Austronesian family as similarities could be seen with bahasa Melayu and it has a few morphological processes involve. Besides, findings also show that Lun Bawang is still being used by the community but some components of endangered language could be seen as most of the people are moving towards official languages which are bahasa Melayu and English.